Upaya Pencegahan Maladministrasi Oleh OMBUDSMAN Republik Indonesia Dalam Meningkatkan Kualitas Pelayanan Publik Di Indonesia - Nurlita Purnama; Annisa Miskiyah; Muhammad Khoirul Anwar (Universitas Katolik Widya Karya Malang, 2023)
The research discusses the Role of Maladministration Prevention by the Ombudsman of the Republic of Indonesia in Improving the Quality of Public Services in Indonesia. This research is based on the many problems of maladministration that occur in Indonesia, for this reason, supervision is needed by the Ombudsman as an external supervisory institution. Oversight by the Ombudsman over the running of government is a guarantee that the state does not lead to an unlimited dictatorship, which is contrary to the characteristics of a rule of law state. This research uses descriptive qualitative research methods with data collection techniques through observation techniques and literature studies. The results show that efforts to prevent maladministration of public services have been carried out by the Ombudsman of the Republic of Indonesia by carrying out various activities to prevent maladministration since the establishment of the Ombudsman. Various efforts in the form of activities have been carried out so that maladministration of public services in Indonesia can be prevented from recurring. There are several activities carried out every year as a form of efforts to prevent maladministration of public services that have been carried out by the Ombudsman. However, the Ombudsman also has obstacles in carrying out his duties and powers as a supervisory institution for the implementation of public services, including a lack of human resources, many people still think that reporting to the Ombudsman will definitely have the same results, there are some people who do not know and feel foreign to the term Ombudsman , the related party (reported) did not follow the Ombudsman's suggestion to make improvements.